Síntese e caracterização do aço Maraging-350 tratado termicamente sob diferentes condições - Nunes, Glécilla Colombelli de Souza (2015)
In this dissertation, we characterized a sample of commercial Maraging-350 steel l and Fe-18Ni-12Co-4,9Mo-1,35Ti alloy. The alloy corresponds to Maraging-350 steel composition and was made by arc-melting (inert atmosphere). The Maraging-350 steel and Fe-18Ni-12Co-4,9Mo-1,35Ti alloy were submitted to different heat treatments, for solubilization in the ? - phase (austenite), followed by cooling to room temperature and also for further aging. The samples were structurally characterized by X-ray diffraction (Rietveld method) and by Mössbauer spectroscopy for the magnetic and hyperfine properties. The results revealed that the cooling induced a martensitic transformation in the system to, crystallizing it into a body-centered cubic structure (martensite). The crystallographic and hyperfine parameters of the alloy found for the two sample groups developed in this work are consistent with those found in the literature for Maraging-350 steels. It was also observed that the aging heat treatments generate the formation of reversed austenite in relative amounts that vary with the temperature and time of treatment, in either the steel or the alloy.